A walk through the progression of resuscitation medicine. Issue 1 (10th October 2020) - Shoaib, Muhammad; Becker, Lance B.
Abstract: Cardiac arrest (CA) is a sudden and devastating disease process resulting in more deaths in the United States than many cancers, metabolic diseases, and even car accidents. Despite such a heavy mortality burden, effective treatments have remained elusive. The past century has been productive in establishing the guidelines for resuscitation, known as cardiopulmonary resuscitation (CPR), as well as developing a scientific field whose aim is to elucidate the underlying mechanisms of CA and develop therapies to save lives. CPR has been successful in reinitiating the heart after arrest, enabling a survival rate of approximately 10% in out‐of‐hospital CA. Although current advanced resuscitation methods, including hypothermia and extracorporeal membrane oxygenation, have improved survival in some patients, they are unlikely to significantly improve the national survival rate any further without a paradigm shift. Such a change is possible with sustained efforts in the basic and clinical sciences of resuscitation and their implementation. This review seeks to discuss the current landscape in resuscitation medicine—how we got here and where we are going. Abstract : Although current advanced resuscitation methods for cardiac arrest, including hypothermia and extracorporeal membrane oxygenation, have improved survival in some patients, they are unlikely to significantly improve the national survival rate any further without a paradigm shift. Such a change is possible with sustained efforts in the basic and clinical sciences of resuscitation and their implementation. This review discusses the current landscape in resuscitation medicine—how we got here and where we are going.